Boko Haram in Context: An Attempt to Solve the Current Campaign of Violence in Nigeria - Solomon, Anjide, Timothy (African Journal of Education,Science and Technology (AJEST), 2016)
Since 2009, there has been violent uprising of Boko Haram in Nigeria. Consequent upon this unfortunate development, therefore, different attempts have been made by scholars to situate boko haram conflict within the broader field of political violence, terrorism and other related theories of conflict. However, different accounts exist within literature on how to identify the cause and motivation of the group’s choice of violent strategy. These accounts which are built on narratives and theories are centred on; socio-economic and political explanations, religious explanation, grievance from the extra-judicial killing of Boko Haram leader, the polarised nature of the Nigerian state and, as well as the influence of international Jihadist movement. However, some of these accounts appear to be insufficient in explaining the phenomenon while others are faulty in terms of the ontology and methodology used in analysing the phenomenon. Poor socio-economic and political situations can be source of peaceful cooperation and not all individuals tend to be violent in the face of deprivations. Before the killing of its leader, Boko Haram under different names was already radicalised. While religion as described by Juergensmeyer (2000) as both vehicle for peace and violence, it will be inappropriate to downplay the role of radical religious ideology due to the; name, mission and similar attributes of Boko Haram with International Jihadist movement. Similar to Wiktorowicz (2006), this paper seeks to argue on Boko Haram within the radical Salafist ideology, thereby situating it within the context of Political Islam. Political Islam is a term which is anchored on belief that the socio-economic and political lives of Muslims should be determined by Islam, it is a fussy term, particularly as it seeks to answer whether it is a “revolution, radicalism or reform”. Consequently, this paper recommends on how both the efforts of moderate and non-violent Muslims and the government can be synchronized towards bringing a sustainable solution to ending the Boko Haram campaign of violence.